1987
DOI: 10.1042/bj2420499
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of horse liver mitochondrial aldehyde dehydrogenase by disulfiram. Evidence that disulfiram is not an active-site-directed reagent

Abstract: The inhibition of mitochondrial (pI 5) horse liver aldehyde dehydrogenase by disulfiram (tetraethylthiuram disulphide) was investigated to determine if the drug was an active-site-directed inhibitor. Stoichiometry of inhibition was determined by using an analogue, [35S]tetramethylthiuram disulphide. A 50% loss of the dehydrogenase activity was observed when only one site per tetrameric enzyme was modified, and complete inactivation was not obtained even after seven sites per tetramer were modified. Modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Kitson (1978) observed that the dehydrogenase activity was more susceptible to disulfiram inhibition than the esterase activity of the sheep enzyme. Nevertheless, disulfiram, which modified the catalytically essential group of sheep liver cAldDH (Kitson 1987), did not react with the essential residue of horse liver mAldDH (Sanny and Weiner 1987). In the present study, both chloral hydrate and disulfiram acted as competitive inhibitors for the esterase and dehydrogenase activities of rat liver of mAldDH.…”
Section: Discussioncontrasting
confidence: 57%
“…Kitson (1978) observed that the dehydrogenase activity was more susceptible to disulfiram inhibition than the esterase activity of the sheep enzyme. Nevertheless, disulfiram, which modified the catalytically essential group of sheep liver cAldDH (Kitson 1987), did not react with the essential residue of horse liver mAldDH (Sanny and Weiner 1987). In the present study, both chloral hydrate and disulfiram acted as competitive inhibitors for the esterase and dehydrogenase activities of rat liver of mAldDH.…”
Section: Discussioncontrasting
confidence: 57%
“…TR was previously shown to inhibit also other enzymes such as aldehyde dehydrogenase, aldehyde oxidase and rat lipoprotein lipase activity in adipose tissue (Freundt and Netz, 1977;Sanny and Weiner, 1987;Sadurska and Boguszewski, 1993). None of these enzymes is copper dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, incorporation could be detected within the first few minutes when ALDH was inhibited by disulfiram [75]. It seems that the ALDH inhibition by disulfiram is caused by the formation of an intramolecular disulfide bond between the active site thiol and the thiol of another cysteine residue [76][77]. Nevertheless, there are other possible mechanisms of disulfiram inhibitory action on ALDH via its metabolites [78][79][80][81][82][83][84].…”
Section: General Biological Activity Of Dithiocarba-matesmentioning
confidence: 99%